Socialization on Stunting Prevention at Tonasa Village, Tombolo Pao District, Gowa Regency - Pianto, Lisa Evelyn; Husain, Firman (Faculty of Engineering UNHAS, 2025)
Stunting is a nutritional problem that is still widespread in Indonesia, so involvement from all parties is very necessary to overcome the stunting problem. Therefore, Hasanuddin University (Unhas) is also actively involved through the Community Service Program (KKN). The causes of stunting are very diverse, such as limited parental knowledge, economic limitations, anemia in pregnant women, and unclean environmental conditions. Children with stunting will experience hampered organ development and are more susceptible to non-communicable diseases (NCDs) such as diabetes, coronary heart disease and stroke. Stunting can be prevented with several efforts, one of them is by providing information to the public regarding the causes and impacts of stunting. Therefore, Unhas KKN students, through the implementation of the Stunting Prevention Socialization work program in Tonasa Village, Tombolo Pao District, are trying to provide knowledge to the community regarding stunting prevention. The stages of implementing the work program are pre-test, socialization, and post-test. Socialization was carried out using posters containing information about stunting and steps to prevent stunting. Based on the results of the pre-test and post-test carried out, it is known that the Stunting Prevention Socialization work program has been 100% successful